The Effectiveness of “Wassam” in Improving Students’ Waqf Stock Literacy - Harpepen, Andi; Yustati, Herlina (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study aims to assess the effectiveness of the Wassam application in improving stock waqf literacy among students of the Faculty of Economics and Islamic Business (FEBI) at UIN Fatmawati Sukarno Bengkulu.Design/methodology: The research employs an experimental design with a one-group pretest-posttest model to measure changes in stock waqf literacy before and after using the Wasam application. A total of 30 students from the 6th semester were selected as the experimental group. Data were analyzed using the Simple Weighted Index method and JASP software.Findings: The results show a significant increase in literacy scores from 71.08 to 95.88, with a paired sample t-test yielding a p-value of <0.001, indicating a statistically significant improvement. This suggests that the Wasam application effectively enhances students’ understanding of stock waqf, supporting previous research and contributing to the development of digital-based waqf education.Practical implications: The findings highlight the potential of digital platforms in improving waqf literacy. The Wasam application can be used as an effective educational tool to increase awareness and understanding of stock waqf among students. Institutions can integrate such applications into their curriculum to further enhance financial literacy and digital waqf adoption.Originality/Value: This study contributes to the limited literature on digital waqf literacy by empirically evaluating the impact of the Wasam application. It provides a novel insight into how digital tools can enhance understanding and engagement with stock waqf, especially among university students.